Design of Ubiquitous Pulse Oximetry - Reza Firsandaya Malik (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
In recent years, people have difficulty to breathe a good air quality. It is caused by vehicle emission, household combustion devices, forest fires, and industrial facilities are regular sources of air pollutants. These air pollutants can impair people health and behavior. It means that decreasing oxygen supply can reduce our immune system. The effect of reducing oxygen in our blood cause rapid fatigue, difficulty breathing, muscle pain, eye irritation and even more severe would have a heart attack. Monitoring peoples' health is one of solutions to increase the quality of human life. The pulse oximetry widely used to measure the oxygen level or oxygen saturation (SpO2) in the blood. While it has long been an important tool in clinical practice, pulse oximetry has become a popular medical tool for outside hospital environment use. Pulse oximetery work by the principles of spectrophotometry: the relative absorption of red (absorbed by deoxygenated blood) and infrared (absorbed by oxygenated blood) light of the systolic component of the absorption waveform correlates to arterial blood oxygen saturations. Patients usually take measure using pulse oxymetry in a stationary condition. While pulse oximetry recording a patient's oxygen level, the finger should not move until the recording is completed. The previous research have been evaluated a pulse oximetry in mobile condition. This paper will investigate the relationship between oxygen saturation and light attenuation in the proposed design of the ubiquitous pulse oximetry in mobile condition. This design will help the future development of SpO2 recording ability while patient in walking condition and give good accuracy as same as off-the-shelf pulse oxymetry.